Things to make and do. - Milbourne, Anna. (Tulsa, OK : EDC Pub., 2005)
Provides instructions for 365 craft projects, including masks, drawings, pop-up cards, collages, and more.
Includes index.
3.1
K-3
Keywords: Drawing -- Juvenile literature; Handicraft -- Juvenile literature; Paper work -- Juvenile literature; Drawing; Handicraft; Paper work; Drawing; Handicraft; Paper crafts